Acute toxicity study of intravenous administration of thymoquinone-loaded nanostructured lipid carrier (TQ-NLC) in Sprague dawley rats - Saiful Yazan, Latifah; Mohd Azlan, Siti Nabilahuda; Zakarial Ansar, Fatin Hannani; Gopalsamy, Banulata (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Thymoquinone (TQ), a bioactive compound from Nigella sativa is known for its various medicinal properties. Due to the low solubility of TQ, nanostructured lipid carrier (NLC) has been used as a delivery system to improve its efficacy. Nevertheless, the effect of TQ-NLC when administered intravenously is unclear. This study investigated the acute toxicity profile of intravenous administration of TQ-NLC in an in vivo model. Methods: Twelve female Sprague dawley rats were assigned randomly into two groups (n=6); a control and a treatment group that received normal saline and 25 mg/kg TQ-NLC, respectively, via intravenous injection. The rats were observed for 14 days for any alterations to their usual physical conditions such as behaviour and mortality, body weight, food intake, organ-to-body weight ratio, and haematological, biochemical and histopathological profile. Results: There were no significant changes (p>0.05) in the body weight, food intake, organ-to-body weight ratio, and haematological, bio-chemical and histopathological profile between TQ-NLC treatment and the control group. However, inflammation was observed at the site of injection on the rat’s tail. Conclusion: Intravenous administration of TQ-NLC (25 mg/kg) did not exert acute toxic effect in female Sprague dawley rats. The data can be used as a basis to further develop TQ-NLC as a potential therapeutic drug.